(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
The basement complex rock that underlies Gora and its surroundings consists primarily of banded and porphyroblastic gneisses, biotite schist, and the minor rocks being pegmatites and quartzo-feldspatic veins. This study aims to characterize, at a 1:25,000 scale, the geology, structure, and geochemistry of the rock units in the Gora region. To attain this aim, field research, petrographic, and geochemical studies were conducted. Quartz, feldspars, biotite, and hornblende were identified as major minerals in petrographic analyses of the gneiss, with muscovite and apatite present in trace amounts. X-ray fluorescence (XRF) analytical methods were used to determine the rocks’ geochemical compositions. Fold, fault, pinch, and swell, and vein sizes were all quantified. Major fractures, joints, and veins all run NW-SE, while smaller ones run NE-SW. The structural NW-SE and NE-SW trends are also reflected in the data that has been linearly analysed (SRTM DEM). The geochemical results obtained revealed that the gneisses and biotite schist are high-K calc-alkaline and orthogneiss derived from igneous protoliths. The gneisses and biotite schist were further classified on the SiO2 vs. FeOt /MgO binary diagram in calc-alkaline series. The gneisses and biotite schist are peraluminous in nature. The gneisses and biotite schist were formed in a passive continental margin tectonic setting.